Study on Human Body Contour Extraction from Images Based on HSV Color Model (Journal of Fiber Bioengineering and Informatics, 2015)
Color is one of the most powerful and important types of visual information. Color information of imagesplays an important role in human body contour extraction process. In most of the current human bodycontour extraction systems, color images are converted into gray images first and then human bodycontours are extracted from these gray images. In this process, a large mount of color information is lostand the extraction results are inaccurate. Besides, strict requirements are put forward about objectiveconditions when taking pictures in these systems, such as background, dress, pixel of cameras, lightand so on. In order to solve these problems, HSV color model in line with human visual habits wasadopted to extract human body contours in this paper. Human body contours were directly extractedfrom color images by analyzing and changing H, S and V values. MATLAB software was used to write ahuman body contour extraction program. Results of experiments show that the accuracy of extractionis improved. The requirements about the background, dress, pixel, light and other factors are reducedthrough adopting HSV color space. Automatic human body contour extraction under complex conditionsis realized in this paper, which can lay a foundation for the development of remote automatic humanbody measurement systems. Research results of this paper provide a reliable basis for the developmentof apparel electronic-commerce and personalized customization.
Keywords: Color Information; Human Body Contour Extraction; Color Images; HSV Color Model; Requirements about Conditions